Profil Kebiasaan Belajar Siswa Bagi Program Bimbingan Belajar - Vinsensius Juma; Maria Erlinda; Dhiu Margaretha (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The title of this thesis is Profile of Study Habits of Class VII A Students of SMPK Sancta Familia Kupang for the 2022/2023 Academic Year. The problems in this study are: 1) What is the profile of study habits of grade VIIA students of SMPK Sancta Familia Kupang for the 2022/2023 academic year? 2) What are the implications of the study habit profile of grade VIIA students of SMPK Sancta Familia Kupang for the 2022/2023 academic year for the tutoring program? The purpose of the study was to find out: 1) Profile of study habits of grade VIIA students of SMPK Sancta Familia Kupang for the 2022/2023 academic year, 2) Implications of the profile of study habits of grade VIIA students of SMPK Sancta Familia Kupang for the 2022/2023 academic year, for the tutoring program. This research method uses quantitative descriptive methods with data collection tools in the form of questionnaires of student study habits. The population and sample of this study are 26 students of grade VII A SMPK Sancta Familia Kupang for the 2022/2023 academic year. The data analysis technique used is central trend analysis. The results of the analysis of research data showed that the average study habits of 140.9730 students were in the range of 120-155 scores, classified as high. It can be interpreted that grade VII A students of SMPK Sancta Familia Kupang for the 2022/2023 academic year have good study habits. This can be seen through student attitudes, namely making study schedules and their implementation, reading and taking notes, completing assignments, how to follow lessons, how to study groups, how to study independently at home. Based on the results of this study, researchers provide advice to: 1) Head Schools are expected to maintain and improve cooperation with BK teachers, facilitate and support all tutoring program designs in schools to be carried out properly in order to maintain good student learning habits. 2) Guidance Teachers Guidance counselors are expected to design and develop tutoring programs to maintain good student study habits. 3) Students are expected to actively utilize tutoring activities carried out by BK teachers to maintain good student study habits.